Efektivitas Program Kredit Usaha Rakyat (KUR) pada Usaha Mikro, Kecil dan Menengah (UMKM) di Kecamatan Kuta Selatan, Kabupaten Badung - Kadju, Daniel; Bendesa, I K G (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2017)
Research was conducted on MSMEs follow KUR program in the district of South Kuta, Badung regency. Samples are taken as many as 68 SMEs within a period of two years (2013-2014), using sampling techniques Probability Sampling, where the probability sampling all elements SMEs follow KUR program in the population are known and have equal opportunities to be elected as a sample. The data collection is done by observation, interview and kueisoner. Data analysis technique used is the test of effectiveness and non-parametric analysis using the Mc Nemar test. Based on the analysis conducted found that the level of effectiveness of the KUR program on SMEs is very effective with a rate of 82.4 percent effectiveness and impact KUR program positively and significantly to increase the amount of work the work, marketing and income generation of MSMEs in the district of South Kuta, Badung , This means KUR program implemented within a period of two years (2013-2014) has been very effective and positive impact and increase the workforce, marketing and revenue SMEs.
Keywords: People' s Business Credit (KUR), Micro, Small and Medium Enterprises and Effectiveness